PENGAPLIKASIAN BIOSAKA DALAM PERTANIAN ORGANIK DI KECAMATAN TANJUNG GADANG - Melinda, Yesi; Hendrita, Vivi; Nurazizah, Wahyuli (LPPM Universitas Malikussaleh - Indonesia, 2024)
Biosaka is a product extracted from plants that thrive and have naturally adapted to their surroundings, helping to effectively repel pests. Especially in Tanjung Gadang, farmers have benefited greatly from the use of Biosaka, which is a collaboration between them and the agricultural extension agency. Using a qualitative method involving observation, field practice, interviews, and reference to relevant documents, the creation of Biosaka has been a very effective solution in overcoming two major problems faced by farmers: pest infestation and high fertilizer costs. Thanks to Biosaka, farmers have not only managed to reduce losses due to pest infestation, but have also been able to manage their expenses more efficiently due to reduced dependence on expensive chemical fertilizers. Research results show that the use of Biosaka has a positive impact on soil fertility and overall plant health. Soils treated with Biosaka become more fertile, increasing crop yields as well as the quality of the plants grown. Plant leaves look greener and fresher, signaling better overall plant health. This not only increases agricultural productivity in Tanjung Gadang, but also helps build a more sustainable and environmentally friendly farming system. By continuing to develop and expand the use of Biosaka, farmers in the region can strengthen their resilience.